Implementation and Evaluation of Infographic Media Interactive Nearpod Assisted Collaborative Learning on Plant Parts - Ramadhani, Suci; Raharjo, Makmum; Suratmi (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
This research aims to develop interactive infographic media, assisted by the Nearpod website, to enhance participation, motivation, and academic achievement among fourth-grade students in learning the material on plant parts. The development model used in this study is ADDIE, which consists of five stages: analysis, design, development, implementation, and evaluation. The research was conducted at SDN 25 Indralaya, involving 31 fourth-grade students. The development process of the interactive media began with an analysis of teachers' and students' needs to assess the learning conditions and media requirements. The media was designed by combining text, images, and videos to create an engaging and informative display. After the design phase, implementation was carried out through trials with students and teachers to evaluate the practicality of using the media. The results of the study show that the developed interactive infographic media effectively increased students' understanding. The N-Gain scores from the students' pretest and posttest reached 0.875, indicating a significant improvement and categorizing the result as high. Additionally, the responses from the questionnaire showed positive feedback from both teachers and students, with satisfaction scores of 100% and 95.6%, respectively. Based on these findings, this study concludes that interactive infographic media, with the assistance of the Nearpod website, can serve as an effective alternative to support the learning process in fourth grade, particularly in understanding plant parts, and demonstrates the potential of information and communication technology in improving the quality of education..